Decoupling analysis of urban water resource utilization and economic development - Qianli, Xu; Hongyao, Sun (Frontiers in Environmental Science, 2025)
The study constructs a decoupling evaluation model, taking Nanjing City as an example. It contributes to a deeper understanding of the sustainable utilization of water resources and the coordination between regional economic development and ecological preservation. In addition, Nanjing’s water resource endowment, social background, economic foundation, and ecological environment have unique characteristics and significance. The results show that (1) the water resource ecological footprint tended to gradually decrease and level off. Water consumption in industry and agriculture was relatively high, and there were imbalances in the consumption and distribution of water resources across different social and economic sectors. (2) The carrying capacity of per capita water resources in Nanjing presented a gradual upward and downward trend, roughly resembling an “M” shape. (3) The average ecological deficit of per capita water resources over the recent 10 years was −0.53 hm2/person. The average ecological pressure index was 4.54. Therefore, this suggests significant pressure on water resource utilization and ecological environment protection. (4) The decoupling rate between water resource utilization and economic development has reached approximately 100%, indicating that economic development can help a city reduce its dependence on water resources. However, the relationship between the development of industry and agriculture and water resource utilization was not well coordinated.